Zanette T. Glørstad and Kjetil Loftsgarden (eds.): Viking-Age Transformations: Trade, Craft and Resources in Western Scandinavia - James Graham-Campbell (Viking, 2018)
Book review, Zanette T. Glørstad and Kjetil Loftsgarden (eds.): Viking-Age Transformations: Trade, Craft and Resources in Western Scandinavia